Implementasi Metode SQ3R Berbantu Media Cerita Bergambar Untuk Meningkatkan Kemampuan Maharah Qira’ah - Muriawati, Nur; Zulliana, Erni; Fauziah, Asti (STAI Syaichona Moh. Cholil Bangkalan, 2024)
The SQ3R reading method is an abbreviation for Survey, Question, Read, Recall / Recite, and Review. This method is highly recommended for reading more deeply and logically due to its structured and practical approach. The SQ3R method aims to help students better remember the material they learn. With the SQ3R learning method, students can study texts effectively, enabling them not only to memorize the content but also to understand the meaning and concepts within the reading. This research is motivated by the lack of qiraah (reading comprehension) skills among students. It is based on observations indicating a lack of innovation and effective teaching methods or materials, resulting in students' diminished interest in learning Arabic. Therefore, appropriate learning materials are needed to improve the learning process. The results of this study indicate that efforts to improve students' qiraah skills have been successful. This is evidenced by the implementation of actions in the second cycle, which saw a significant improvement. Out of 37 students, 30 students (81.5%) completed the task successfully, while 7 students (18.5%) did not. This shows an increase of 49% by employing the SQ3R method assisted by picture story media. Based on the research findings and data analysis, it can be concluded that the application of the SQ3R method with the assistance of picture story media can enhance students' qiraah skills.